PENGARUH STRUKTUR AKTIVA, NON DEBT TAX SHIELD, UMUR PERUSAHAAN DAN INVESTASI TERHADAP STRUKTUR MODAL: STUDI PADA PERUSAHAAN BARANG KONSUMSI - Suherman, Suherman; Khodijah, Siti; Ahmad, Gatot (Lembaga Penerbitan Unversitas Esa Unggul, 2017)
The purpose of this study is to examine the effect of assets structure, non-debt tax shield, firm age, and investment on capital structure. This research employs panel data analysis. Sample covers 32 consumer goods firms listed on Indonesian Stock Exchange between 2009 and 2013. The results show that assets structure and non-debt tax shield (NDTS) have negative and significant effect on capital structure. Firm age has positive and significant effect on capital structure. While, investment has positive but insignificant effect on capital structure. Â Keywords: capital structure, assets structure, non-debt tax shield